2017
DOI: 10.18632/oncotarget.15974
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of hexokinase 2 overexpression in solid tumors of digestive system: a meta-analysis

Abstract: Several previous studies have reported the prognostic value of hexokinase 2 (HK2) in digestive system tumors. However, these studies were limited by the small sample sizes and the results were inconsistent among them. Therefore, we conducted a meta-analysis based on 15 studies with 1932 patients to assess the relationship between HK2 overexpression and overall survival (OS) of digestive system malignancies. The relationship of HK2 and clinicopathological features was also evaluated. Hazard ratio (HR) or odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…Moreover, given its selective expression in tumors, HK2 has drawn increasing attention on its clinical implications forming the basis of fluorodeoxyglucose F-18 positron emission tomography imaging, a widely used clinical procedure to detect tumors. Indeed, a recent meta-analysis provides evidence that HK2 could be a marker to predict the risk of all-cause mortality and cancer progression in patients with tumors of the digestive system (31).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given its selective expression in tumors, HK2 has drawn increasing attention on its clinical implications forming the basis of fluorodeoxyglucose F-18 positron emission tomography imaging, a widely used clinical procedure to detect tumors. Indeed, a recent meta-analysis provides evidence that HK2 could be a marker to predict the risk of all-cause mortality and cancer progression in patients with tumors of the digestive system (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is the dysfunction of cancer cell metabolism that conferred the Warburg Effect 152 , while targeting this phenotype could be a strategy to expose tumour in an unfavourable micro-environment. This hypothesis has inspired many scientists to focus on several enzymes that would be crucial in the process of cell metabolism, such as glucose transporters (GLUTs) 153 , hexokinase2 (HK2) 154 , pyruvate kinase M2 (PKM2) 155 , pyruvate dehydrogenase kinase (PDK) 156 , and lactate dehydrogenase-A (LDHA) 157 . A number of inhibitors that target those specific enzymes have been developed as potential anti-cancer agents 158 .…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05 produce glucose-6-phosphate [31]. Previous studies have confirmed that the expression of HK2 is significantly upregulated in many cancers and its high expression in cancers is associated with poor prognosis [30,[32][33][34][35]. Administration of HK2 inhibitor, 2-DG, can induce cancer cell death by abrogating intracellular glycolysis.…”
Section: Discussionmentioning
confidence: 97%